Influence of Microstructure and Texture on Tensile Properties of an As-Rolled Ti2AlNb-Based Alloy - Caihong Jing; Shoujiang Qu; Aihan Feng; Hao Wang; Daolun Chen (Metals, 2025)
Ti2AlNb-based alloys are widely used in aerospace applications due to their excellent high-temperature mechanical properties. This study aims to investigate the texture, microstructural evolution, and phase transformation behavior of Ti2AlNb-based alloy sheets during heat treatment and their effects on tensile properties. During heat treatment, B2 → O phase transformation occurs at 550 °C and 650 °C, while Ostwald ripening takes place at 700 °C and 850 °C. The α2 phase undergoes spheroidization around 1000 °C due to grain boundary separation and recrystallization. Additionally, the B2, O, and α2 phases all exhibit strong textures. The B2-phase texture follows a cubic orientation ({100}<001>), rotated ~30° around the normal direction (ND). The O-phase texture consists of a strong {100}<010> rolling texture and a weaker texture component <001>//RD, influenced by the B2-phase texture, rolling deformation, and variant selection during O-phase precipitation. Each B2 grain generates four variants, forming distinct O-phase textures within the same grain. The α2-phase texture exhibits typical rolling textures, [0001]//TD, <<semantics><mover accent="true">1¯</mover></semantics>2<semantics><mover accent="true">1¯</mover></semantics>0>//ND, and {11<semantics><mover accent="true">2¯</mover></semantics>0}<01<semantics><mover accent="true">1¯</mover></semantics>0>, remaining stable after heat treatment. Tensile tests show that the rolled sheet has better ductility along the rolling direction (RD), while the transverse direction (TD) demonstrates higher yield strength (up to 1136 MPa). The anisotropy in tensile properties is mainly attributed to the O-phase texture, with minor contributions from the α2-phase and B2-phase textures. These findings provide a theoretical basis for optimizing the mechanical properties of Ti2AlNb-based alloys.